Agricultural City - its Formal Shape in the Light of Historic Theoretical Designs and Emerging Technologies - Rudnicka-Bogusz, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The progressive degradation of environment and urban sprawl inspired the search for alternative ways of urban development. In this context, the concept of a "regenerative city" has gained significant traction in the field. It encompasses a variety of principles and strategies to ensure that cities can function sustainably and do not just consume resources but also actively regenerate them. In this context, the role of urban farming is particularly relevant.
Keywords: urban agriculture; urban farm; agricultural city; urban resilience; sustainable development